Equatorial spread F: Statistical comparison between ionosonde and scintillation observations and longitude dependence - Iyer, K.N.; Jivani, M.N.; Pathan, B.M.; Sharma, S.; Chandra, H.; Abdu, M.A. (My University, 2003)
Spread F on ionograms and scintillations of trans-ionospheric signals arise from unstable structure of the ionospheric F-region occurring predominantly by night. The two techniques were applied to two pairs of sites in India, one near the magnetic equator and the other near the northern crest of equatorial ionization anomaly. At both pairs of sites no similarity of the statistical patterns derived from the two techniques was found except during solar maximum epoch. At the magnetic equator, scintillation and range spread F occur predominantly during premidnight period of equinoxes and increase with solar activity. At the anomaly crest, scintillation occurrence is generally rarer than at the magnetic equator with some exceptions. Post midnight scintillations are, predominant in summer, and generally decrease with increase in solar activity. A striking feature is a modest increase with solar activity at anomaly crest but an enormous one at the equator. Comparison of spread F occurrence at Indian and Brazilian equatorial locations show, unexpectedly, quite different statistics. This is attributed to the different magnetic declination angles at the two sites.
Keywords: Equatorial spread F; Scintillation observation; Magnetic equator; F-region